Errors made by academicians in writing journal articles - Dea Analisti; Siti Rohani (Jurnal Linguistik Terapan, 2018)
Writing and publishing journal articles is challenging and yet developing the academicians’ way of thinking to get not only the value of writing process but also recognition from others. However, there are a lot of difficulties encountered including grammatical and syntactical problems. This study focused on analysing the errors made by academicians when writing journal articles and identifying the influencing factors for the errors made. This case study was conducted by examining ten journal articles written by non-English Department lecturers. The error analysis on the journal articles included the sentence types, the sentence logic, and the sentence errors. Then, further analysis was made regarding the possible influencing factors on the errors made. Findings show that the most frequent sentence type was complex sentences. In terms of sentence logic, the numbers of sentences written correctly were in a high percentage and the most of sentences were also well structured. In other words, the sentence logic in the journal articles was considered as good. In addition, the most common errors found in the journal articles were more related to the use of conjunctions. The influencing factors for the errors included the lack of assessment of the writing quality and lack of extensive editing on the part of the journal editor. In conclusion, the authors were suggested to take editing services for reviewing process or to ask for assistance from experienced colleagues for several revisions in order to improve the quality of journal articles and avoid unnecessary errors.